Anna Cooper and Nannie Burroughs: Educating head, heart, and hand in the early 20th century African American community - Jovita Ross-Gordon; LaVerne Gyant (Adult Education Research Conference, 1993)
The contributions and holistic educational philosophies of Anna Cooper and Nannie Burroughs are examined as examples of the "neglected histories" of adult education. Also discussed are their perspectives on issues of race and gender.